Contraction-Induced Loss of Plasmalemmal Electrophysiological Function Is Dependent on the Dystrophin Glycoprotein Complex - Baumann, Cory W.; Lindsay, Angus; Sidky, Sylvia R.; Ervasti, James M.; Warren, Gordon L.; Lowe, Dawn A. (Frontiers in Physiology, 2021)
Weakness and atrophy are key features of Duchenne muscular dystrophy. Dystrophin is one of the many proteins within the dystrophin glycoprotein complex (DGC) that maintains plasmalemmal integrity and cellular homeostasis. The dystrophin-deficient mdx mouse is also predisposed to weakness, particularly when subjected to eccentric (ECC) contractions due to electrophysiological dysfunction of the plasmalemma. Here, we determined if maintenance of plasmalemmal excitability during and after a bout of ECC contractions is dependent on intact and functional DGCs rather than, solely, dystrophin expression. Wild-type (WT) and dystrophic mice (mdx, mL172H and Sgcb-/- mimicking Duchenne, Becker and Limb-girdle Type 2E muscular dystrophies, respectively) with varying levels of dystrophin and DGC functionality performed 50 maximal ECC contractions with simultaneous torque and electromyographic measurements (M-wave root mean square [M-wave RMS]). ECC contractions caused all mouse lines to lose torque (p < 0.001), however deficits were greater in dystrophic mouse lines compared to WT mice (p < 0.001). Loss of ECC torque did not correspond to a reduction in M-wave RMS in WT mice (p = 0.080), while deficits in M-wave RMS exceeded 50% in all dystrophic mouse lines (p ≤ 0.007). Moreover, reductions in ECC torque and M-wave RMS were greater in mdx mice compared to mL172H mice (p ≤ 0.042). No differences were observed between mdx and Sgcb-/- mice (p ≥ 0.337). Regression analysis revealed ≥ 98% of the variance in ECC torque loss could be explained by the variance in M-wave RMS in dystrophic mouse lines (p < 0.001) but not within WT mice (R2 = 0.211; p = 0.155). By comparing mouse lines that had varying amounts and functionality of dystrophin and other DGC proteins, we observed that (1) when all DGCs are intact, plasmalemmal action potential generation and/or conduction is maintained, (2) deficiency of the DGC protein β-sarcoglycan is as disruptive to plasmalemmal excitability as is dystrophin deficiency and, (3) some functionally intact DGCs are better than none. Our results highlight the significant role the DGC plays in maintaining plasmalemmal excitability, and that a collective synergism (via each DGC protein) is required for this complex to function properly during ECC contractions.